The relationship between school-related gender-based violence and absenteeism: Evidence from 14 Southern and Eastern African countries - Sora Lee; Robert Rudolf (South African Journal of Education, 2022)
Children in sub-Saharan African countries face higher exposure to gender-based violence (GBV) compared to their counterparts in other world regions (United Nations Children’s Fund [UNICEF], 2014). When GBV occurs in schools, it severely endangers access to education. Using the third round of data of the Southern and Eastern Africa Consortium for Monitoring Educational Quality (SACMEQ) from over 60,000 Grade 6 learners across 14 countries, we examined the relationship between GBV in primary schools and learners’ absenteeism. Findings indicate that sexual harassment perpetrated by teachers significantly increases learners’ absenteeism. In contrast, effects were less clear when the perpetrator was a fellow learner. Effects found are similar in magnitude for girls and boys. Violence prevention education programmes and stricter punishment for offenders are needed to establish a safer school environment and overcome harassment-related barriers to learning.